2011
DOI: 10.1080/08952841.2011.540487
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Application of the Transtheoretical Model During Strength Training in Older Women

Abstract: A Transtheoretical Model (TTM) goal-setting tool was used during strength training in women. Volunteers (mean age = 69, N = 27) were assigned to a strength training only or strength training/behavior change 12-week intervention. A pre/posttest, quasiexperimental design assessed TTM constructs, Health-Related Quality of Life, and functional fitness measurements. Multiple ANCOVAs revealed significant differences between groups on lower body strength (p = .001), upper body flexibility (p = .002), Decisional Balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The three intervention studies reviewed, which represent the highest quality evidence, had mixed results. Fetherman et al 59 showed changes in RT participation did not track to changes in self-efficacy, while Lubans et al 45 found that changes in RT participation and self-efficacy were not associated in mediation analyses. By contrast, Millen and Bray72 showed changes in self-efficacy partially mediated the relationship between the intervention and changes in RT participation.…”
Section: Resultsmentioning
confidence: 99%
“…The three intervention studies reviewed, which represent the highest quality evidence, had mixed results. Fetherman et al 59 showed changes in RT participation did not track to changes in self-efficacy, while Lubans et al 45 found that changes in RT participation and self-efficacy were not associated in mediation analyses. By contrast, Millen and Bray72 showed changes in self-efficacy partially mediated the relationship between the intervention and changes in RT participation.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the semi-structured focus group format allowed for open responses and for participants to share stories not related to their physical condition or perceived health. This allowed for the opportunity to learn more about the nuanced role of social relationships and CBFP participation of older women (Fetherman et al, 2011). Lastly, socioemotional selectivity theory (Carstensen, 1995) was used as a theoretical framework to better understand how older women prioritize participation in the CBFP (Gardiner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Performing strength training in a group setting or considering alternative muscle strengthening activities may also positively influence affect and, ultimately, strength training participation. Specifically, strength training participation may be higher in a group setting vs. an individual setting, as demonstrated by Fetherman et al (2011), who showed 88% adherence to strength training in a group setting compared to 49% in an individual setting over the same period [ 55 ]. Sports are also often overlooked as forms of muscle strengthening activities.…”
Section: Discussionmentioning
confidence: 99%